PENGARUH PENAMBAHAN LIMBAH KARET SOL SEBAGAI SUBSTITUSI AGREGAT KASAR PADA CAMPURAN BETON TERHADAP KUAT LENTUR - Nursani, Rosi; Hasna Arsalani, Ismi; Kurnia Hidayat, Asep (Universitas Perjuangan Tasikmalaya, 2022)
Abstract—Concrete is the most widely consumed building material product besides water. More environmentally friendly concrete (green concrete) is defined as concrete that at least uses waste materials as one of its components, or its production does not cause environmental damage. In rigid pavements the strength against traffic loads is expressed by the flexural tensile strength of the concrete. If reinforcement is used, it is for crack control only and not for traffic loading. Rubber sole waste is used as a substitute for coarse aggregate in concrete mixtures. This research was conducted to determine the effect of the addition of rubber sole waste on the flexural strength of concrete. The test specimens were in the form of blocks with dimensions of 15 x 15 x 60 cm with variations in the addition of rubber sole waste of 0%, 4%, 8% and 12% of the volume of coarse aggregate. The design concrete quality is 25 MPa with flexure tests at the ages of 7, 14, 21 and 28 days. The results of the study at 28 days of concrete flexural strength showed that a mixture with a percentage of rubber sole waste 4% of coarse aggregate produced a flexural strength value of 5.44 MPa 6.88% higher than normal concrete which produced a flexural strength value of 5.09 MPa. While the percentage of 8% and 12% experienced a decrease in flexural strength compared to normal concrete which resulted in flexural strength values of 4.71 MPa and 4.18 MPa. Substitution of rubber sole waste in the concrete mixture of 4% by weight of coarse aggregate can increase the value of the flexural strength of concrete and is a mixture that produces optimal strength in concrete. Keywords — Concrete, Flexural Strength, Rubber Sole Waste. Abstrak—Beton merupakan produk bahan bangunan yang paling banyak dikonsumsi selain air. Beton yang lebih ramah lingkungan (green concrete) didefinisikan sebagai beton yang setidaknya menggunakan bahan limbah sebagai salah satu komponennya, atau produksinya tidak menyebabkan kerusakan lingkungan. Dalam perkerasan kaku kekuatan terhadap beban lalu lintas dinyatakan dengan kuat tarik lentur dari beton. Jika penulangan digunakan, penulangan hanya untuk mengontrol retak dan bukan untuk memikul beban lalu lintas. Limbah karet sol digunakan untuk substitusi agregat kasar pada campuran beton. Penelitian ini dilakukan untuk mengetahui pengaruh penambahan limbah karet sol terhadap kuat lentur beton. Benda uji berupa balok dengan dimensi 15 x 15 x 60 cm dengan variasi penambahan limbah karet sol sebesar 0%, 4%, 8% dan 12% dari volume agregat kasar. Mutu beton rencana yaitu 25 Mpa dengan uji lentur pada umur 7, 14, 21 dan 28 hari. Hasil penelitian pada umur 28 hari, kuat lentur beton menunjukkan bahwa campuran dengan persentase limbah karet sol 4% dari agregat kasar menghasilkan nilai kuat lentur 5,44 Mpa lebih tinggi 6,88% dibandingkan dengan beton normal yang menghasilkan nilai kuat lentur 5,09 Mpa. Sedangkan presentase 8% dan 12% mengalami penurunan kuat lentur dibandingkan dengan beton normal, yang menghasilkan nilai kuat lentur 4,71 Mpa dan 4,18 Mpa. Substitusi limbah karet sol pada campuran beton sebesar 4% dari berat agregat kasar dapat meningkatkan nilai kuat lentur beton dan merupakan campuran yang menghasilkan kekuatan optimal pada beton. Kata kunci—Beton, Kuat Lentur, Limbah Karet Sol.